EFFORTS MANAGEMENT OF TINEA CORPORIS IN A 16-YEARS-OLD FEMALE PATIENT THROUGH A FAMILY MEDICINE APPROACH AT MUARA BATU PRIMARY HEALTH CENTER, NORTH ACEH REGENCY - Yuliana (Jurnal Medika Hutama, 2026)
Patient Mrs. S, came with her aunt to the Muara Batu Health Center with complaints of itching on the body area with circular spots that began to spread to the back, groin, legs and hands since 7 months ago and worsened in the last 2 weeks. The spots appear round with reddish-colored raised edges with firm borders accompanied by fine scales. Complaints are aggravated when sweating, especially when exposed to sunlight and patients often scratch the lesion to reduce the complaints felt. The assessment was carried out through autoanamnesis, physical examination and home visits. The clinical picture leads to a skin infection in the form of tinea corporis. Interventions carried out include education about the causes of tinea corporis to patients, education about personal and environmental hygiene, avoiding the use of common items (clothes, towels) to prevent the risk of transmission, the use of topical drugs and regular medication.